Capital structure decisions under the German tax code - Peter Nippel (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2006)
We consider the tax advantage of an increase in the firms leverage under the German tax code. The analysis is performed (i) for the case of a given investment and future dividend policy and (ii) to decide on the relative tax advantage of debt versus equity for funding new investments. We start with a more general model to derive simple conditions for a tax advantage of debt under a "classical" tax system. Additionally we show that under our assumption of a given future investment policy capital gains taxes do not matter for the capital structure decision. In the second part we include more particularities of the German tax code, i.e. the corporate tax in combination with the trade tax (Gewerbesteuer), the personal tax with a rebate for equity income (i.e. the Halbeinkünfteverfahren), and we account for the different treatment of short and long term debt under the trade tax.
Keywords: G32; 650; Capital structure; German Tax Code; Kapitalstruktur; Unternehmensbesteuerung; Betriebliche Finanzwirtschaft; Theorie; Deutschland